Free Serratus Fascia Flap for Reconstruction of Soft Tissue Defects Involving the Distal Upper and Lower Extremity. Issue 6 (June 2020) - Tuncer, Serhan; Sezgin, Billur; Sencan, Ayse; Sari, Alper
Abstract : Background: Free fascial flaps are widely used for the reconstruction of defects located on the distal extremities as they provide thin yet durable soft tissue coverage. The serratus anterior fascia flap stands out from other fascial flap alternatives as it has optimal anatomical properties that can provide ideal coverage in a wide range of reconstructive challenges. The purpose of this study was to present our experience with the serratus anterior fascia flap in a variety of complex soft tissue defects. Methods: A retrospective review was conducted on patients who underwent reconstruction with the free serratus anterior fascia flap for complex soft tissue defects involving the distal extremities. Results: Complex soft tissue defects of 13 patients were reconstructed using the free serratus fascia flap. No major postoperative complications such as flap loss, dehiscence, infection, or hematoma were encountered in any of the patients. All of the patients demonstrated durable and harmonious long-term flap coverage that facilitated movement without any signs of scar contractures and tendon adhesions at the site of reconstruction. Conclusions: The serratus anterior fascia flap demonstrates versatility and stability for the closure of complex distal extremity defects. It creates thin yet durable coverage that facilitates underlying tendon gliding while providing harmony with the natural contours of these anatomic areas and has low donor site morbidity, making it a primary choice in the reconstruction complex soft tissue defects involving the hands and feet.